2020
DOI: 10.3354/meps13257
|View full text |Cite
|
Sign up to set email alerts
|

Non-targeted tourism affects the behavioural budgets of bottlenose dolphins Tursiops truncatus in the South Adriatic (Montenegro)

Abstract: We investigated the short-term effects of non-targeted tourism on the behaviour of bottlenose dolphins Tursiops truncatus in the South Adriatic off the coast of Montenegro, by comparing dolphin group behaviour during impact (the presence of non-targeted tourism vessels) and control (absence of all marine vessels) scenarios. Tourism vessel and dolphin behavioural data were collected through systematic weekly land-based surveys. Using instantaneous focal ‘group’ scan sampling, the predominant behaviour of bottle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 52 publications
1
15
1
Order By: Relevance
“…Following interactions with NTBs, dolphins increased their milling behaviour, with a significant decrease in their foraging behaviour. Although research throughout the Adriatic Sea has previously indicated that foraging behaviours are increased during spring and summer (Bearzi et al, 1999;Bearzi et al, 2008b;Affinito et al, 2018;Clarkson et al, 2020) and milling behaviours are least observed during the same seasons (Affinitio et al, 2018;Clarkson et al, 2020), the current study demonstrates a significant increase in milling behaviour upon interaction with NTBs which cannot be attributed to seasonality.…”
Section: Discussioncontrasting
confidence: 65%
See 4 more Smart Citations
“…Following interactions with NTBs, dolphins increased their milling behaviour, with a significant decrease in their foraging behaviour. Although research throughout the Adriatic Sea has previously indicated that foraging behaviours are increased during spring and summer (Bearzi et al, 1999;Bearzi et al, 2008b;Affinito et al, 2018;Clarkson et al, 2020) and milling behaviours are least observed during the same seasons (Affinitio et al, 2018;Clarkson et al, 2020), the current study demonstrates a significant increase in milling behaviour upon interaction with NTBs which cannot be attributed to seasonality.…”
Section: Discussioncontrasting
confidence: 65%
“…Significant decreases in foraging behaviour (which include diving and surface feeding behaviours) in bottlenose dolphins have also been reported elsewhere in the Adriatic Sea, despite much lower association rates with NTBs (Clarkson et al, 2020). It is well established that reductions in foraging behaviour reduce the energy intake of dolphins (Williams et al, 2006;Christiansen et al, 2010) and can lead to detrimental implications on the chances of survival and reproductive success if repeated disruptions occur (Lusseau, 2003;Constantine et al, 2004;Lusseau et al, 2006).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations